2020
DOI: 10.1128/jb.00547-19
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Regulators MntR and Zur Participate in Redox Cycling, Antibiotic Sensitivity, and Cell Wall Plasticity

Abstract: The Bacillus subtilis MntR and Zur transcriptional regulators control homeostasis of manganese and zinc, two essential elements required in various cellular processes. In this work, we describe the global impact of mntR and zur deletions at the protein level. Using a comprehensive proteomic approach, we showed that 33 and 55 proteins are differentially abundant in ΔmntR and Δzur cells, respectively, including proteins involved in metal acquisition, translation, central metabolism, and cell wall homeostasis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…ZnO NPs may also release cytotoxic Zn 2+ ‐ions upon their partial dissolving (Vidic et al., 2014). Namely, ZnO NPs can release Zn 2+ ‐ions intracellularly that disturb bacterial redox potential (Randazzo et al., 2020). Seray et al.…”
Section: Nanofillersmentioning
confidence: 99%
“…ZnO NPs may also release cytotoxic Zn 2+ ‐ions upon their partial dissolving (Vidic et al., 2014). Namely, ZnO NPs can release Zn 2+ ‐ions intracellularly that disturb bacterial redox potential (Randazzo et al., 2020). Seray et al.…”
Section: Nanofillersmentioning
confidence: 99%
“…In contrast with pfeT mutants, it has been reported that mntR mutants are more H 2 O 2 -sensitive than WT in LB medium [15, 49]. However, this phenotype is very sensitive to the precise metal content of the medium.…”
Section: Resultsmentioning
confidence: 99%
“…However, high concentrations of Mn ions (of about 66.42 mM) observed in LB medium will hardly be tolerated by bacterial cells, because intracellular metal homeostasis in bacteria is ensured by nely tuned import and efflux systems. 45 It seems that both hydrogen ion generation and Mn-ion release of FeMnO 3 particles induce strong DPPH radical scavenging indicating an antioxidant effect.…”
Section: Antioxidant Recovery Activitymentioning
confidence: 99%
“…Previous studies have shown that bacterial cells may neutralize H 2 O 2 by catalyse or some superoxide enzymes, and in such way cope with acute oxidative stress. 7,45 We next sought to evaluate for any potential cytotoxicity of FeMnO 3 dissolved in bacterial media. The impact of different concentrations of FeMnO 3 was studied by measuring grown kinetics of a B. subtilis hospital isolate (NDMed).…”
Section: Bacterial Growth Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation